Polymorphic display and texture integrated systems controlled by capillarity - Ha, Jonghyun; Kim, Yun Seong; Li, Chengzhang; Hwang, Jonghyun; Leung, Sze Chai; Siu, Ryan; Tawfick, Sameh (Science Advances, 2023)
Soft robotics offer unusual bioinspired solutions to challenging engineering problems. Colorful display and morphing appendages are vital signaling modalities used by natural creatures to camouflage, attract mates, or deter predators. Engineering these display capabilities using traditional light emitting devices is energy expensive and bulky and requires rigid substrates. Here, we use capillary-controlled robotic flapping fins to create switchable visual contrast and produce state-persistent, multipixel displays that are 1000- and 10-fold more energy efficient than light emitting devices and electronic paper, respectively. We reveal the bimorphic ability of these fins, whereby they switch between straight or bent stable equilibria. By controlling the droplets temperature across the fins, the multifunctional cells simultaneously exhibit infrared signals decoupled from the optical signals for multispectral display. The ultralow power, scalability, and mechanical compliance make them suitable for curvilinear and soft machines.
Keywords: Colorful displays; Energy; Engineering problems; Integrated systems; Light-emitting device; Morphing; Rigid substrates; Soft robotics; Switchable; Visual contrast; Animal Fins; Animals; Capillary Action; Electronics; Engineering; Robotics